All Days 2008
DOI: 10.2118/116673-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sand or Mud Removal in Low Bottom Hole Pressure Wellbores Using Jet Pump and Concentric Coiled Tubing Leads to Improved Production

Abstract: Horizontal drilling and completion are common practice for accessing conventional and heavy oil reservoirs. During the drilling process, the formation pore pressure is less than the drilling fluid's hydrostatic pressure. This can lead to some fluid loss before a filter cake is formed to prevent further mud losses. For unconsolidated formations, it is prefer to keep the filter cake in the place to maintain the hole's integrity during the well completion period while running the liner. However, the filter cake c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…While this technology was proven onshore (Benzaquen et al 2006;Kuchel et al 2002;Li et al 2008a;Hibbeler et al 2002) and in offshore Alaska (Rafferty et al 2007), there had been no application in the North Sea, and there was therefore very limited knowledge of the technology locally. CCTVT consists of a CT string inside CT, where circulated liquid is used to activate a jet pump to suck well fi ll into the CT and circulate it back to surface.…”
Section: Ct Reverse Circulation With Nitrifi Ed Fluidmentioning
confidence: 99%
“…While this technology was proven onshore (Benzaquen et al 2006;Kuchel et al 2002;Li et al 2008a;Hibbeler et al 2002) and in offshore Alaska (Rafferty et al 2007), there had been no application in the North Sea, and there was therefore very limited knowledge of the technology locally. CCTVT consists of a CT string inside CT, where circulated liquid is used to activate a jet pump to suck well fi ll into the CT and circulate it back to surface.…”
Section: Ct Reverse Circulation With Nitrifi Ed Fluidmentioning
confidence: 99%
“…The main advantages of this technology are its ability to minimize liquids pumped into the well, its independence of reservoir pressure, and its ability to remove liquid at the end of operations to ensure the well can be returned to production. Whilst this technology was proven onshore 6,7,8,9 and in offshore Alaska 10 , there had been no application in the North Sea, and therefore very limited knowledge of the technology locally. Operational data also showed that the technology had never been applied at the reservoir depths of the Ravenspurn North field, and the additional weight of the concentric coiled tubing was recognized as a challenge with limited crane capacity and deck loading on the small ST3 platform.…”
Section: Concentric Coiled Tubing Vacuum Technologymentioning
confidence: 99%
“…The sand/well vacuuming technology has been developed and proven by field operations [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] worldwide to clean out wellbores with a low bottom hole pressure. The sand/well vacuuming technology has been developed and proven by field operations [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] worldwide to clean out wellbores with a low bottom hole pressure.…”
Section: Introductionmentioning
confidence: 99%